HUBUNGAN ANTARA AKTIVITAS FISIK DAN ANGKA KECUKUPAN GIZI MAKRONUTRIEN TERHADAP RASIO KOLESTEROL TOTAL/HDL PADA MASYARAKAT PEDESAAN - Utari Febrina Supomo Sunu; Galih Permadi; Fenty Fenty (Sanata Dharma University, 2017)
Cardiovascular disease is the number one cause of death in the world. The diseaseis influenced by several factors such as lack of physical activity, imbalanced nutritional intake, and high blood cholesterol levels. The value of the total cholesterol / HDL can predict cardiovascular disease risk factors. The study aims to investigate the relationship between physical activity and Dietary Allowances of the macronutrient and ratio total cholesterol / HDL in rural communities. This is observational analytic with cross-sectional design of the 102 respondents (male: 40, female: 62) in Kepuharjo village, Cangkringan, Sleman, Yogyakarta, with a purposive sampling techniques. Physical activity data were taken using a structured interview (Baecke) and Semi Quantitive Food Frequency Questionnaire (SQFFQ) for data macronutrient, while blood total cholesterol and HDL-cholesterol levels were analyzed using enzymatic methods. The results of the study showed that there is no significant relationship between physical activity and the ratio of total cholesterol / HDL (p = 0.038; CI 95%: 0.98-61.33), dietary allowances of the macronutrient energy and the ratio of total cholesterol / HDL (p = 0.068), protein intake on the ratio of total cholesterol / HDL (p = 1.000), fat intake to the ratio of total cholesterol / HDL (p = 0.081), and the intake of carbohydrates to the ratio of total cholesterol / HDL (p = 0.088). In conclusion there is no significant relationship between physical activity and dietary allowance of macronutrient towards to the ratio of total cholesterol / HDL.